The effect of fertilization with the digestate on the quality and chemical composition of selected plants intended for biogas production - Witorożec-Piechnik, Agata; Matyka, Mariusz; Woźniak, Marek; Oleszek, Marta (Polish Journal of Agronomy, 2022)
The aim of the studies was to determine the effect of fertilization with mineral fertilizers and the digestate from an agricultural biogas plant on selected plant parameters. In 2016 a three-year two-factor field experiment was established, where the first factor was the fertilization variant and the second factor was the plant species (triticale, maize, sorghum). Fertilization was carried out on two dates: pre-sowing and top-dressing. The first variant consisted of nitrogen fertilization, exclusively mineral; in the second variant, plants were fertilized before sowing with di- gestate, and then top-dressed with mineral fertilizer; while in the third variant, in both terms, plants were fertilized with digestate. The quality of biomass was examined in terms of its chemical composition and as a raw material for biogas production. Regard- less of the applied variant of fertilization, the plants tested were equally well supplied with nitrogen. Fertilization with digestate increased the C:N ratio in the biomass of sorghum (which de- viated from the optimal value for effective anaerobic fermenta- tion process), lowered the crude fibre content in the biomass of triticale, but also increased the content of cellulose in triticale. Fertilization with digestate makes it possible to give up mineral nitrogen fertilization, without negative influence on the quality and chemical composition (including crude fibre and lignin frac- tions) of triticale and maize used as biogas substrates.